Surface electromyographic analysis of differential effects in kettlebell carries for the serratus anterior muscles - Alex Caravan; John O. Scheffey; Sam J. Briend; Kyle J. Boddy (PeerJ, 2018)
The purpose of this study was to examine differences in the Electromyography (EMG) amplitude of the serratus anterior between 45° kettlebell carries and 90° kettlebell carries. Thirty-three men aged roughly between 19 and 23 and who were either college or professional baseball pitchers were chosen and randomly assigned to either perform the 45° kettlebell carry followed by the 90° kettlebell carry (n = 17) or the 90° kettlebell carry followed by the 45° kettlebell carry (n = 16). Each pitcher was instructed in the proper usage of the exercise and assigned a short break between the two carries. Changes in EMG amplitude were examined after proper band-pass filtering, normalization, and moving average-smoothing of the raw EMG signal. Differences of the EMG amplitude mean frequencies were examined between each subject’s individual carries and the clumped groups of all 45° and 90° carries. Among each individual comparison, eight pitchers had “large” Effect Size differences between the EMG amplitudes of their two carries, with seven of them signaling the 45° carry as the larger value. In addition, when examining the grouped mean differences of the EMG amplitudes, we found the 45° carries to be significantly higher (p-value of 0.018).